Positive Weighted Partitions Generated by Double Series - Andrews, George E.; El Bachraoui, Mohamed (Symmetry, Integrability and Geometry: Methods and Applications, 2025)
We investigate some weighted integer partitions whose generating functions are double-series. We will establish closed formulas for these -double series and deduce that their coefficients are non-negative. This leads to inequalities among integer partitions.